Trends in the number of cardiac surgical procedures after the introduction of routine catheter intervention for isolated congenital shunt lesions - Gautam, Navin Chandra; Basnet, Nishesh; Aryal, Marisha; Joshi, Rheecha; Pradhan, Rupak; Yadav, Ramborash; Shakya, Lalita; Adhikary, Parash; Rajbhandari, Nivesh; Timila, Rabindra Bhakta (Nepalese Heart Journal, 2022)
Background and Aims: The study aimed to evaluate the trends in the number of cardiac surgeries after the introduction of routine catheter intervention for isolated shunt lesions. Methods: A retrospective observational study was conducted which studied the trends in the total number of cardiac surgeries from 2012 to 2019 with the introduction of catheter interventions for isolated shunt lesions for the same period in Shahid Gangalal National Heart Center, Kathmandu, Nepal. The change in the total number of surgeries and surgeries for isolated shunt lesions after the start of the catheter intervention was evaluated. The pre-catheter intervention era and catheter intervention era spanned from 2012 to 2015 and 2016 to 2019 respectively. Results: During the catheter intervention era, out of total 2590 isolated shunt lesions, 1300 were closed by catheter intervention procedure (50%). Only 44%, 11%, and 90 % of Atrial Septal Defect, Patent Ductus Arteriosus and Ventricular Septal Defect respectively were closed surgically. Interestingly, even after introduction of catheter intervention, both the total number of surgeries and surgeries for congenital heart disease (CHD) did not decrease and remained above 1200 and 500 cases per annum respectively. The expected increment in the surgical number for most of the years was achieved following the country’s population growth remained at 1.8%, even though a large portion of isolated shunt lesions were closed by catheter intervention procedure. Conclusion: Though a significant number of isolated shunt lesions were closed by catheter intervention procedure, the number of surgical procedures for congenital as well as total cardiac surgeries did not decrease in number.